The enjoyment of sanctioned aggression in rugby: The experience of a pioneering female Canadian team captain - Kerr, J. H. (International Journal of Sport and Exercise Psychology, 2019)
The aim of the present qualitative case study was to examine the motivational experiences of a Canadian pioneering female rugby player with a particular focus on her insider experiences of sanctioned and unsanctioned aggression in rugby. Reversal theory was the theoretical framework that guided the study. A retrospective semi-structured interview was used. The findings indicated that her two primary motives for playing rugby were the enjoyment of physical contact (sanctioned aggression) and being a serious, physically fit, elite athlete playing rugby for the Canadian national team. In her interview statements, the participant recounted incidents where she was the recipient of illegal acts of unsanctioned aggression by opponents in international games. Also, as the perpetrator of two minor acts of unsanctioned anger aggression incited by opponents, the participant experienced unpleasant psychological responses. The results confirm the importance of sanctioned aggression in the motivation of a female rugby player and support reversal theory concepts and findings from previous research on different types of aggression in male team contact sports. As an important new case study, the findings add to the very limited previous published research on psychological aspects of women`s participation in rugby. The findings also have cautious relevance to understanding the role that physical contact and sanctioned play aggression may have in other women`s motivation for playing rugby. Suggestions are made for future qualitative research on aggression in women`s rugby with larger samples.